Deposition and characterization of RF-sputtered-Ta2O5 thin films for O2 reduction reaction in polymer electrolyte membrane fuel cells (PEMFC) - Samsudin N.; Ferdaous M.T.; Shahahmadi S.A.; Mustafa S.N.; Akhtaruzzaman M.; Sopian K.; Chelvanathan P.; Amin N. (Elsevier GmbH, 2023)
Annealing; Catalysts; Cyclic voltammetry; Deposition; Electrolytic reduction; Gas fuel purification; Polyelectrolytes; Polymer films; Structural properties; Substrates; Tantalum oxides; Thin films; Orthorhombic phasis; Oxygen reduction reaction; Potentiostatic electrolysis; Rate of deposition; Silicon substrates; Substrate temperature; Ta2O5 thin films; Ta2O5sputtering; Proton exchange membrane fuel cells (PEMFC)